Work Life Balance Problems of Industrial Workers in Kerala: A Study in the Perspective of Toiling Class Theory - Dhanabhakyam, M.; Fahad K.P (Jurnal Multidisiplin Madani, 2024)
Since human resources are assets to the organizations, it is important to draw attention to their work life balance aspect. It is highly important in the industrial sector where the employees have to devote a lion’s share of their time for work and are hardly striving to balance their work lives and personal lives. The Toiling Class theory propounded by late former minister Sri KM Mani, clearly points out the relevance of work life balance. According to this theory, there are two classes of working people which include ruling class and toiling class where the latter (toiling class) is prone to the exploitation of the former (ruling class). Such exploitation probably results in detrimental effect on the work life balance of the toiling class.  The researcher aims to analyze the work life balance of industrial workers in Kerala. A convenient sample of 116 industrial workers working in different industries in Kozhikode, Malappuram and Ernakulam Districts of Kerala were selected as a part of the study. Average Score Analysis, Independent sample t test and One Way ANOVA are the statistical tools used by the researcher for analyzing the Work Life Balance problems of the respondents. The results of analysis showed that there is moderate to high existence of work life balance problems or work life imbalances among the respondents. Various concerns of work life imbalance incorporated from the previous studies have proved to be the effect on the employees in the present study also. The findings of the present study provide worthy suggestions to the researchers, academicians and policy makers to understand and consider the work life balance problems of the industrial workers in Kerala